Multilingual Approaches for Teaching and Learning 2020
DOI: 10.4324/9780429059674-12
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the partnership between language minority parents and professionals in early childhood education and care: a systematic review

Abstract: Exploring the partnership between language minority parents and professionals in early childhood education and care. A systematic review.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Some policymakers and ECEC (Early Childhood Education and Care) professionals, for instance, still advise against multilingual child-rearing (e.g. Kirsch 2012;Aghallaj et al 2020), causing parents raising their family in a multilingual context even more concern about the linguistic, cognitive and socio-emotional development of their children.…”
Section: Introductionmentioning
confidence: 99%
“…Some policymakers and ECEC (Early Childhood Education and Care) professionals, for instance, still advise against multilingual child-rearing (e.g. Kirsch 2012;Aghallaj et al 2020), causing parents raising their family in a multilingual context even more concern about the linguistic, cognitive and socio-emotional development of their children.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, another systematic review (Aghallaj et al, 2020) was found using a reference list search (Booth et al, 2022). This review includes research conducted between 2000 and 2018.…”
Section: Previous Researchmentioning
confidence: 99%
“…This review includes research conducted between 2000 and 2018. Throughout the three systematic reviews, the focus is on collaboration between ECEC institutions and multilingual parents, and all the reviews are based on research and theories that frame collaboration as meaningful and beneficial to children's learning and development (Aghallaj et al, 2020;Norheim & Moser, 2020;Tveitereid, 2018).…”
Section: Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, there has been a shift in the attitude towards bi-/multilingualism, with an increasing emphasis on the positive side effects and benefits for children's linguistic, cognitive, socio-emotional and cultural development. However, on the practical level, much depends on the context, the setting, the country, and the language and education policies, which are not always supportive of multilingual child-rearing practices (Aghallaj et al, 2020;Kirsch, 2012). The FLP, efforts at language management, ideologies, implicit and explicit language choices, as well as the parental language use, strategies, beliefs, attitudes, practices, well-being, and affective factors, influence children's language outcomes (Caldas, 2012;Fogle, 2013).…”
Section: Family Language Policymentioning
confidence: 99%